Lophiostomin A–D: new 3, 4-dihydroisocoumarin derivatives from the endophytic fungus Lophiostoma sp. Sigrf10. Issue 12 (14th February 2020) - Mao, Ziling; Xue, Mengyao; Gu, Gan; Wang, Weixuan; Li, Dianpeng; Lai, Daowan; Zhou, Ligang
Abstract : Four new 3, 4-dihydroisocoumarin congeners, named lophiostomin A–D (1–4 ), together with two known α-pyridones (5 and 6 ) were isolated from cultures of the endophytic fungus Lophiostoma sp. Sigrf10 obtained from Siraitia grosvenorii . Abstract : Four new 3, 4-dihydroisocoumarin congeners, named lophiostomin A–D (1–4 ), together with two known α-pyridones (5 and 6 ) were isolated from cultures of the endophytic fungus Lophiostoma sp. Sigrf10 obtained from Siraitia grosvenorii . The structures of the new compounds were determined via combined analysis involving 1D and 2D NMR, high-resolution electrospray ionization mass spectrometry (HRESIMS), and electronic circular dichroism (ECD) spectra, as well as quantum chemical ECD computations for assigning the absolute configurations. All the compounds were evaluated for their antibacterial and antifungal activities. Compounds 1 and 2 displayed moderate inhibitory activities against the spore germination of Magnaporthe oryzae, whereas 5 and 6 were active against the following tested pathogenic bacteria: Bacillus subtilis, Agrobacterium tumefaciens, Ralstonia solanacearum, and Xanthomonas vesicatoria .